Response of Arabidopsis thaliana seedlings to lead exposure: effect of pre-treatment with sodium nitroprusside - Phang, Ing Chia; Leung, David W. M.; Taylor, H. Harry; Burritt, David J. (2009)
Plants are regularly exposed to unfavorable conditions that impose stress. Lead (Pb), is one of the major pollutants in the environment that causes serious public health and environmental concerns. Increasing levels of lead could also have severe consequences for plants. Plants exposed to lead stress initiate signaling pathways, and make specific changes in their cell physiology and metabolism to avoid or tolerate the stress. However, mechanisms to reduce the effects of lead may vary from plant to plant, developmental stage, and culture medium.